Investigation of negative emotions and sleep quality in gastric cancer patients and intervention strategies - Wang, Gang; Zhang, Quanquan; Pan, Shengjie (Frontiers in Neurology, 2025)
ObjectiveThis study investigates the prevalence of negative emotions and sleep disturbances in gastric cancer patients, explores their relationship, and suggests targeted interventions to enhance their physical and mental well-being.MethodsA total of 650 gastric cancer patients from the First Affiliated Hospital of Soochow University (March 2020 to March 2023) were included. Negative emotions, including anxiety and depression, were assessed using the Positive and Negative Affect Schedule (PANAS), while sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI). Descriptive statistics and Pearson correlation analysis were employed to analyze the data and explore the relationship between negative emotions and sleep quality.ResultsOf the 650 patients, 533 (82%) exhibited negative emotions, and 560 (86.15%) experienced sleep disturbances. A significant positive correlation was found between negative emotion scores and sleep quality (r = 0.682, p < 0.05). Patients with poor sleep quality had significantly higher negative emotion scores (p < 0.05). Factors such as gender, age, tumor stage, and education level influenced negative emotion scores, while room type significantly impacted sleep quality (p < 0.05).ConclusionNegative emotions and sleep disturbances are common and interrelated in gastric cancer patients. Addressing psychological factors, particularly anxiety and depression, is crucial for improving sleep quality and overall recovery. Integrated psychological and sleep management interventions should be incorporated into routine care to improve patients’ quality of life and treatment outcomes.